EFFECT OF VITAMINS NICOTINIC ACID, PYRIDOXINE AND Co2+, Mn2+, Cu2+ METAL-IONS ON CRITICAL MICELLE CONCENTRATION OF ANIONIC, CATIONIC AND NONIONIC SURFACTANTS IN AQUEOUS SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Effect of aqueous soluble vitamins nicotinic acid, pyridoxine and biologically active ions Co2+, Mn2+, Cu2+ on critical micelle concentration (cmc) of anionic surfactant sodium pentadecylsulfonate, cationic surfactant cetylpyridinium bromide and nonionic surfactant hexadecylpoly[oxyethylene(20)] alcohol (C16A20) in aqueous solutions at 303.15 K was studied. It was shown that with increase of vitamins concentration the cmc of studied anionic sodium pentadecylsulfonate increases and cmc of C16A20 decreases. In the presence of metal-ions cmc of the studied surfactants decreases.
Keywords: micellization, sodium pentadecylsulfonate, cetylpyridinium bromide, hexadecylpoly[oxyethylene(20)] alcohol